Effect of solution chemistry on the transport of short-chain and long-chain perfluoroalkyl carboxylic acids (PFCAs) in saturated porous media. (September 2022) - Qi, Lin; Li, Runwei; Wu, Yudi; Lin, Xinsong; Chen, Gang
Abstract: Perfluorocarboxylic acids (PFCAs) are one of the most widely detected classes of PFAS in the global environment after decades of intensive use. This study investigated the impact of perfluorinated carbon chain length on the transport behavior of PFCAs by testing and modeling two short-chain (PFPeA and PFHxA) and two long-chain PFCAs (PFOA and PFDA) in laboratory water-saturated columns. Moreover, their transport behavior was examined under different solution chemistry conditions, including pH, ionic strength, and cationic type. The experimental and simulation results indicated that the chain length had a limited impact on transport behaviors of PFPeA, PFHxA, and PFOA under various pH and ionic strengths, evidenced by their tracer-like breakthrough curves. In contrast, the mobility of PFDA was significantly affected by pH and ionic strengths. Additionally, the transport of all four PFCAs was inhabited in the presence of the divalent cation Ca 2+ . This study could help predict migration behavior and assess the potential risk of PFCAs in the subsurface system. Graphical abstract: Image 1 Highlights: Short-chain and long-chain PFCAs show distinct difference transport behavior in saturated porous media. pH and ionic strengths had limited impact on PFPeA, PFHxA, and PFOA mobility. Long-chain PFDA was sensitive to environmental chemistry changes. Divalent cation, i.e.Ca 2+, can enhance retardation of PFCAs in the sand column.